Orthopedic patients’ satisfaction towards perioperative nursing care in Hospital Universiti Sains Malaysia - Shueib, Siti Sarah (2020)
Patient ‘s satisfaction is one of the main indicators of patient experience about health care services and quality of care provided. Previous study found that orthopedic patient satisfaction with perioperative care remains largely undiscovered, with only a few researches available. Thus, the purpose of this study is to determine the level of orthopedic patients’ satisfaction towards perioperative nursing care provided in Hospital USM. The number of population in this study was 60 orthopedic patients that were admitted for perioperative care in the orthopedic surgical ward at Hospital USM. The research design was a cross-sectional and quantitative study. The sampling method used is a non-probability method via purposive sampling method by using Good Perioperative Nursing Care Scale questionnaire (GPNCS). The result showed that the level of satisfaction among orthopedic patients is good (M=4.09, SD=0.56). The highest mean score for domain of GPNCS is physical care (M=4.35, SD=0.68) and the lowest mean score domain are support (M=3.60, SD=0.61) and nursing process (M=3.60, SD=1.11). Highest mean item of GPNCS are received sufficient pain medication (M=4.73, SD=0.78) and placed in a comfortable surgical position on the operating room table (M=4.73, SD=0.78). The lowest item of GPNCS is chance to listen to music if wanted to (M=2.93, SD=1.49). There is no significant different between age (p=0.075), gender (p=0.143), level of education (p=0.179), employment status (p=0.706) and type of anesthesia (p=0.123) with perioperative nursing care provided. Overall, patients who are below 30 years, male, secondary education, employed and those who undergoing surgery with regional anesthesia are more satisfied with perioperative nursing care provided.